Tax Competition Or Tax Coordination? What Is Better For The European Union? - Działo, Joanna (Comparative Economic Research. Central and Eastern Europe, 2015)
Tax competition is defined as the use of tax policy that will allow to maintain or increase the attractiveness of a particular territory for business location. Tax competition is used especially by the relatively under-developed countries, as foreign capital inflow gives them the possibility to implement modern technology, new management methods, or to increase exports. One of the effects of tax competition is the formation of tax havens, i.e. countries or territories offering preferential tax rates in order to gain capital from abroad. A comparative analysis of the income tax rates in the EU countries and certain tax havens shows that despite the progressive reduction of the rates of these taxes in the EU, the phenomenon of tax competition is still very strong, and the position of tax havens as countries with relatively low or very low taxes seems to be unthreatened. The question arises whether tax competition is a real problem for the EU Member States and if there exist arguments for tax harmonization, or at least tax coordination within the EU countries. The discussion in this paper suggests that the arguments for tax coordination in the EU are not yet strong enough. However, both tax competition and tax coordination have their supporters and opponents.